Understanding Careers Around the Globe: Stories and Sourcebook - Jon Briscoe; Michael Dickmann; Douglas T. Hall; Wolfgang Mayrhofer; Emma Parry (Edward Elgar Publishing, 2023)
This fascinating book comprises case studies of careers from 24 countries across the globe, highlighting culture-specific career issues, and encouraging reflection on one's own career. Interwoven with current theoretical and empirical insights from career studies, it emphasises the importance of our respective contextual settings. Reflecting socio-political changes around the globe, the book discusses a range of factors that can influence career success, including personal characteristics, stability and change, boundaries and borders, and gender. Chapters examine key themes such as career reinvention, professional resilience in times of financial crisis, support for immigrants in transitioning to local labour markets, and the effect of Brexit on career motivations, across countries including Argentina, Canada, India, Japan, Nigeria, and Switzerland. Throughout the book, contributors consider three defined perspectives on careers - ontic, spatial, and temporal - to identify the fundamental aspects of careers around the world. Proposing new solutions to contemporary career issues, this book will be vital reading for students and teachers of human resource management, international business, organisational behaviour, economics and finance. It will also be beneficial for guidance counsellors, careers advisers and coaches, and HR professionals.
Keywords: 330; Careers; career success; careers in different countries; career success factors; culture and careers; institutions and careers; Beruf; Karriereplanung